Piezoelectric Layer Transfer Process for MEMS - Gwenael Le Rhun; Franklin Pavageau; Timothée Rotrou; Christel Dieppedale; Laurent Mollard (Proceedings)
Piezoelectric MEMS devices were fabricated on 200 mm Si wafers using both deposited and layer-transferred PZT films. In both cases, the PZT-based devices showed ferroelectric and piezoelectric properties at the level of current state-of-the-art devices. The wafer-to-wafer piezoelectric layer transfer process that was developed can thus be useful to bypass the thermal budgeting issue associated with the high crystallization temperature of PZT (~700 °C). It allows the integration of PZT capacitors on any kind of layer stack or substrate, for either actuator or sensor applications.